Recent developments in nanomaterials for upgrading treatment of orthopedics diseases - Shang, Jinxiang; Zhou, Chao; Jiang, Chanyi; Huang, Xiaogang; Liu, Zunyong; Zhang, Hengjian; Zhao, Jiayi; Liang, Wenqing; Zeng, Bin (Frontiers in Bioengineering and Biotechnology, 2023)
Nanotechnology has changed science in the last three decades. Recent applications of nanotechnology in the disciplines of medicine and biology have enhanced medical diagnostics, manufacturing, and drug delivery. The latest studies have demonstrated this modern technology's potential for developing novel methods of disease detection and treatment, particularly in orthopedics. According to recent developments in bone tissue engineering, implantable substances, diagnostics and treatment, and surface adhesives, nanomedicine has revolutionized orthopedics. Numerous nanomaterials with distinctive chemical, physical, and biological properties have been engineered to generate innovative medication delivery methods for the local, sustained, and targeted delivery of drugs with enhanced therapeutic efficacy and minimal or no toxicity, indicating a very promising strategy for effectively controlling illnesses. Extensive study has been carried out on the applications of nanotechnology, particularly in orthopedics. Nanotechnology can revolutionize orthopedics cure, diagnosis, and research. Drug delivery precision employing nanotechnology using gold and liposome nanoparticles has shown especially encouraging results. Moreover, the delivery of drugs and biologics for osteosarcoma is actively investigated. Different kind of biosensors and nanoparticles has been used in the diagnosis of bone disorders, for example, renal osteodystrophy, Paget's disease, and osteoporosis. The major hurdles to the commercialization of nanotechnology-based composite are eventually examined, thus helping in eliminating the limits in connection to some pre-existing biomaterials for orthopedics, important variables like implant life, quality, cure cost, and pain and relief from pain. The potential for nanotechnology in orthopedics is tremendous, and most of it looks to remain unexplored, but not without challenges. This review aims to highlight the up tp date developments in nanotechnology for boosting the treatment modalities for orthopedic ailments. Moroever, we also highlighted unmet requirements and present barriers to the practical adoption of biomimetic nanotechnology-based orthopedic treatments.